Input voltage/current distortion in switch-mode power supplies & filtering, their cost and benefits - Thong, Tiong Peng (2019)
We explore various types of DC-to-DC converter and its characteristics of Switch Mode Power Supply (SMPS) in this study. A designed buck converter in a closed-loop feedback circuit with the proportional integration (PI) controller is examined using estimation and tuning methods. We analyze the efficiency and effectiveness of SMPS topologies in terms of the system requirements for the ripple control of the output waveform and the total harmonic distortion (THD). We apply transfer function to examine the stability of the designed circuit using bode plot and pole and zero analysis. The experiment results are consistent with the outcomes of the transfer function. Our results show that the level of voltage and current ripple is optimum at 5%. However, the open-loop DC-to-DC converter is not regulated at the desired output voltage and it serves only one fixed equipment with a constant power rating. Thus, we develop the cheapest and effective closed-loop buck converter which allows a flexible power output rating ranging from 50w to 500w without affecting the output voltage. Finally, we construct an analogue circuit using operational amplifier (Op amp) to design the PI controller for the voltage control loop. The results show the overdamping transient waveform with a short duration stabilizes rapidly and a constant power is achieved. Overdamping is resulted from the lagging of the electronic components instead of a digital controller.The long-term cost and benefit for the proportional integration derivative (PID) controller is worth studied as the electronic giants face a high competition in developing a high efficient chips for future green energy sector.